4-Component correlated all-electron study on Eka-actinium Fluoride (E121F) including Gaunt interaction: Accurate analytical form, bonding and influence on rovibrational spectra - Amador, Davi H.T.; de Oliveira, Heibbe C.B.; Sambrano, Julio R. [UNESP]; Gargano, Ricardo; de Macedo, Luiz Guilherme M. (Elsevier, 2016)
A prolapse-free basis set for Eka-Actinium (E121, Z = 121), numerical atomic calculations on E121, spectroscopic constants and accurate analytical form for the potential energy curve of diatomic E121F obtained at 4-component all-electron CCSD(T) level including Gaunt interaction are presented. The results show a strong and polarized bond (≈181 kcal/mol in strength) between E121 and F, the outermost frontier molecular orbitals from E121F should be fairly similar to the ones from AcF and there is no evidence of break of periodic trends. Moreover, the Gaunt interaction, although small, is expected to influence considerably the overall rovibrational spectra.